The intensification of milk production and the quality of dairy marketing - Teufel, Nils; Duncan, Alan J.; Singh, V.K.; Mekonnen, Kindu (International Livestock Research Institute, 2011)
Dairy production has long been recognised for its potential to reduce poverty of smallholder mixed farmers. However, milk production can only generate income where dairy marketing institutions exist. Yet even where milk is sold, milk is often produced as very low levels of intensity, despite many attempts to increase animal productivity. On the other hand, one can find examples of intensified dairy production, often where the quality of milk marketing institutions is above average. However, few studies have attempted to gather data to specifically address the issue of how the quality of milk marketing is linked to the intensity level of milk production. India, the world's biggest milk producer, and Ethiopia, home to the second-largest population of poor livestock keepers in sub-Saharan Africa, are suitable objects for such an investigation. They include areas where milk marketing is well established and the various forms of production intensification, mostly improving genetics and feeding, are widely accepted. On the other hand, large areas, often located in marginal regions, are hardly linked to dairy markets and milk is produced with only minimal yield-increasing inputs. However, most small-holder milk producers are situated in intermediate conditions with some opportunities to sell milk and using low levels of external inputs, such as concentrates. In the present study, 176 group interviews in 90 villages selected according to the quality of their milk markets in three Indian states and two Ethiopian regions were conducted in conjunction with interviews of 76 milk buyers and 30 district key informants to collect data on production intensity and milk marketing. The results indicate that although concentrate feeding and stall feeding increase with improved marketing quality, milk yields of the various dairy animal types (i.e. local cattle, cross-bred cattle, buffaloes) hardly vary. However, the proportion of cross-bred cattle being kept shows the greatest variation by marketing quality amongst all considered indicators. Thus, it appears that improved dairy market opportunities allow households to invest in higher-grade dairy animals as the fastest approach to increase animal productivity. However, the question how dairy development stakeholders can maintain such productivity growth remains to be answered.